2022
DOI: 10.3390/ijms23136934
|View full text |Cite
|
Sign up to set email alerts
|

Novel Drugs with High Efficacy against Tumor Angiogenesis

Abstract: Angiogenesis is involved in physiological and pathological processes in the body. Tumor angiogenesis is a key factor associated with tumor growth, progression, and metastasis. Therefore, there is great interest in developing antiangiogenic strategies. Hypoxia is the basic initiating factor of tumor angiogenesis, which leads to the increase of vascular endothelial growth factor (VEGF), angiopoietin (Ang), hypoxia-inducible factor (HIF-1), etc. in hypoxic cells. The pathways of VEGF and Ang are considered to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 229 publications
0
38
0
1
Order By: Relevance
“…Indeed, Sorafenib, a potent kinase inhibitor and anti-cancer molecule, seems to sequester YAP, thereby facilitating formation of the SRF/MYOCD complex and expression of VSMC-specific contractile genes ( Huang et al, 2019 ). However, Sorafenib is a non-specific inhibitor of growth factor receptors known to impair EC proliferation and tumoral angiogenesis ( Liu et al, 2006 ; Qi et al, 2022 ), which may impair endothelium repair and prolong the need for anti-thrombotic similarly to paclitaxel and Sirolimus.…”
Section: Treatment Of Intimal Hyperplasiamentioning
confidence: 99%
“…Indeed, Sorafenib, a potent kinase inhibitor and anti-cancer molecule, seems to sequester YAP, thereby facilitating formation of the SRF/MYOCD complex and expression of VSMC-specific contractile genes ( Huang et al, 2019 ). However, Sorafenib is a non-specific inhibitor of growth factor receptors known to impair EC proliferation and tumoral angiogenesis ( Liu et al, 2006 ; Qi et al, 2022 ), which may impair endothelium repair and prolong the need for anti-thrombotic similarly to paclitaxel and Sirolimus.…”
Section: Treatment Of Intimal Hyperplasiamentioning
confidence: 99%
“…However, the secretory pathway or mechanism in cardiovascular disease needs further study. Studies have shown that HSP90 mediates AngII-induced vascular smooth muscle cell (VSMC) proliferation and remodeling, and brain microvascular injury during hypertension [ 20 , 72 , 73 ]. Adventitial remodeling is involved in the evolution of several vascular diseases including hypertension [ 74 ].…”
Section: Hsp90 and Cardiovascular Diseasementioning
confidence: 99%
“…HSP90 can be thought of as a “molecular buffer” that maintains the general balance and fidelity of cell signaling, and HSP90 inhibitors are being investigated for the treatment of various conditions [ 16 ]. In addition to their development in cancer therapy, HSP90 inhibitors have important roles in the treatment of many inflammatory diseases [ 6 , 7 , 17 , 18 , 19 , 20 ]. At the same time, they can be used as a target for the treatment of cardiovascular disease (CVD) [ 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other effects of HSPs that could be employed for the development of anti-cancer therapies is their potential antiangiogenic properties which were reported by several studies [ 39 , 40 , 41 , 42 ]. HSP90 inhibitors exert antiangiogenic effects by affecting the PI-3K/AKT and eNOS signal transduction pathways in endothelial cells [ 43 ].…”
Section: Introductionmentioning
confidence: 99%